PEMBELAJARAN TARI PIRING PADA SISWA KELAS VII DI SMP NEGERI 2 SUMEDANG - Mustikawati, Fitria Mayang (2014)
Skripsiiniberjudul "Pembelajarantaripiringpadasiswakelas vii di SMP Negeri 2 Sumedang".Permasalahan yang diangkatadalahkurangnyamotivasisiswadalammengikutipembelajaransenitaridisebabkanoleholehpenerapanmetodedanbahan ajar yang kurangbervariasi.Atasdasaritu, makadapatdirumuskan "Bagaimana proses danhasilpembelajarantaripiringpadasiswakelas vii di SMP Negeri 2 Sumedang?".Tujuanpenelitianiniuntukmeningkatkanmotivasisiswamelaluipembelajarantaripiring.Metode yang digunakanadalahmetodedeskriptifanalisis, dimaksudkanuntukmemotretfenomenapembelajaran yang terjadi di lapangan.Dari hasilpenelitianmenunjukanbahwataripiringmerupakansalahsatumateripembelajarantari yang daparmengakomodirsiswalaki-lakidanperempuan.Jugataripiringcukupmudahuntukdiikuti.Dengandemikian, dapatdisimpulkanbahwapembelajarantaripiringdapatmeningkatkanmotivasisiswadalammengikutipembelajarantari.Untukitudiharapkanpenelitianinidapatdimanfaatkanolehberbagaipihakpenyelenggaraanpendidikansehinggamotivasibelajarsiswameningkat. Kata Kunci :Pembelajaran, TariPiring This thesis entitled "Plate Dance Lessons in class VII in SMP Negeri 2 Sumedang". Issues raised is the lack of student motivation in learning the art of dance to follow due to the application of teaching methods and materials that are less varied. On that basis, it can be formulated "How the process and outcomes of learning dance at the plate in the seventh grade students of SMP Negeri 2 Sumedang?" The purpose of this study is to increase student motivation through learning dance a plate. The method used is descriptive method of analysis, intended to photograph the phenomenon of learning that takes place in the field. From the results of the study show that dance is one of the dishes dance learning materials that can accommodate boys and girls. Also dancing dishes are quite easy to follow. It can be concluded that learning dance plate can improve students' motivation in learning a dance to follow. This study is expected to be used by many education providers to increase student motivation. Keyword :Learning, taripiring